Comparison of 3D printed prostate models with standard radiological information to aid understanding of the precise location of prostate cancer: A construct validation study - Ebbing, Jan; Jäderling, Fredrik; Collins, Justin W.; Akre, Olof; Carlsson, Stefan; Höijer, Jonas; Olsson, Mats J.; Wiklund, Peter N. (PLOS ONE, 2018)
Background To investigate the reliability with which healthcare professionals with different levels of expertise are able to impart the exact location of prostate cancer (PCA) after (A) reading written magnetic resonance imaging (MRI) reports, (B) attending MRI presentations in multidisciplinary team meetings (MDT), and (C) examining 3D printed prostate models, which represents a new technology to describe the location of PCA lesions. Methods We used three different PCA cases to assess the three information tools. Construct validation was performed using two healthcare groups with different levels of expertise: (1) Nine expert urologists in PCA, and (2) nine medical students. After each information tool, the study participants plotted the tumor location in a 2-dimensional prostate diagram. A scoring system was established to evaluate the drawings in terms of accuracy of plotting tumor position. Data are shown as median scores with interquartile range. Results Within the expert group, no significant difference was seen in the overall scoring results between the information tools (p = 0.34). Medical students performed significantly worse with MDT information (p = 0.03). Experts performed better in all three information tools compared to students, resulting in a significantly 25% higher overall total score (25.0[22.3–26.7] vs. 20.0[15.0–24.0], p<0.001). The difference was largest after MDT information, with experts showing a 49% better scoring (p<0.001), and second largest with the 3D printed models, showing a 17% better scoring of the experts (p = 0.07). No difference was found in the written MRI report scoring results between experts and students. Conclusions 3D printed models provided better orientation guide to medical students compared to MDT MRI presentations. This indicates that the 3D printed models might be easier to understand than the current gold standard MDT conferences. Therefore, 3D models may play an increasingly important role in providing guidance for orientation for less experienced individuals, such as surgical trainees.